2021
DOI: 10.3390/heritage4030133
|View full text |Cite
|
Sign up to set email alerts
|

Economic Valuation of Cultural Heritage Using the Travel Cost Method: The Historical Centre of the Municipality of Bucharest as a Case Study

Abstract: Because heritage buildings represent a special category of goods due to characteristics such as uniqueness and irreversibility, they are associated with multiple possibilities of use. This article aims to present a complex analysis of the values associated with using heritage buildings in the historical center of Bucharest and their correlation with corresponding conservation measures using the travel cost method. The authors used two computation methods: the zonal travel cost and the individual travel cost me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…e results showed that the independent variables: total expenditure, monthly income, gender, marital status, family number, and family work, were the effects in the model. Merciu et al [18] evaluated the economic value of cultural heritage based on the travel cost method to make a complex analysis of the relevant value of the heritage buildings of the Bucharest historical center.…”
Section: Tourism Mechanism Integrating Cultural Heritagementioning
confidence: 99%
“…e results showed that the independent variables: total expenditure, monthly income, gender, marital status, family number, and family work, were the effects in the model. Merciu et al [18] evaluated the economic value of cultural heritage based on the travel cost method to make a complex analysis of the relevant value of the heritage buildings of the Bucharest historical center.…”
Section: Tourism Mechanism Integrating Cultural Heritagementioning
confidence: 99%
“…From a methodological point of view, the evaluation of cultural heritage is a difficult process due to the fact that it has multiple socio-cultural values (historical, social, symbolic, aesthetic) that overlap with economic value [13,14]. At the same time, cultural heritage properties can generate various direct and indirect social uses, as well as economic benefits that can be assessed from an economic perspective [14,15,16].…”
Section: Methodsmentioning
confidence: 99%
“…Playing the role of a capital city for centuries, Bucharest has long developed its hospitality services and gastronomy, offering real gastronomic experiences and intercultural interactions [27] within its traditional restaurants, which are often located in emblematic historical heritage buildings [70]. These units offer Romanian dishes, advertising authentic bio-products from branded rural areas and following original recipes [71].…”
Section: Defining Authentic Romanian Gastronomy and Romanian-themed T...mentioning
confidence: 99%
“…Overlapping the nucleus from which the development of medieval Bucharest started, the area named the Old Center of Bucharest is located near the ruins of the old royal courtyard and contains numerous heritage buildings, many of which are being reused for entertainment and catering purposes [70,81]. This happened after 1990 and especially after 2000, when restitution laws allowed the transformation of buildings and ownership changes, restoring the traditional hospitality function for this area in Bucharest (Figure 3).…”
Section: Authentic Gastronomy and Romanian-themed Restaurants In The ...mentioning
confidence: 99%